Effectiveness Of Reproductive Health Education Through Leaflets And Personal Hygiene Practices On Menstrual Knowledge And Behavior Of Vocational School Students In West Java - Indah Yuliani; Nanda Rizka Salsabila (Jurnal Ners, 2026)
Background Adolescent girls are a group that is vulnerable to reproductive health problems, particularly during menstruation, due to low levels of knowledge and inappropriate personal hygiene practices. Data show that the incidence of reproductive health problems among adolescents in Indonesia, including in the city of West Java, remains high. Reproductive health education through easily understandable media, such as leaflets accompanied by personal hygiene practice, is needed to improve knowledge and to develop healthy menstrual behavior. Purpose of Writing This study aims to determine the effectiveness of reproductive health education delivered through leaflets and personal hygiene practice in improving menstrual knowledge and behavior among female students of health vocational high school FISH West Java. Research Method This research used a quantitative design with a quasi-experimental one-group pre-test and post-test method. The sample consisted of 34 female students of health vocational high school FISH West Java selected using purposive sampling. The intervention consisted of reproductive health education delivered through leaflets and personal hygiene practice. Data were collected using questionnaires on menstrual knowledge and behavior. Data were analyzed using the Dependent t-test or Wilcoxon test, according to data distribution. Research Results The results showed an increase in the level of knowledge and personal hygiene behavior during menstruation among female students of health vocational high school FISH West Java after receiving reproductive health education through leaflets and personal hygiene practice. The mean knowledge score increased from 56.47 in the pre-test to 82.35 in the post-test. Meanwhile, the mean personal hygiene behavior score increased from 58.12 in the pre-test to 85.29 in the post-test. Statistical analysis using the Dependent t-test/Wilcoxon test showed a p-value ≤ 0.05, indicating a statistically significant difference before and after the intervention. These findings demonstrate that reproductive health education through leaflets and personal hygiene practice is effective in improving students’ menstrual knowledge and personal hygiene behavior. Conclusion and Suggestions Reproductive health education delivered through leaflets and personal hygiene practice has been proven effective in improving menstrual knowledge and personal hygiene behavior among female students of health vocational high school FISH West Java. Therefore, schools are recommended to implement reproductive health education programs regularly by utilizing simple and practical educational media as an effort to promote adolescent health.